Pelatihan Penggunaan Google Form Sebagai Media untuk Pengumpulan Data Bagi Anggota Pemberdayaan Kesejahteraan Keluarga (PKK) di Desa Turus Gede Kecamatan Rembang Kabupaten Rembang - Sri Suwitri; Endang Larasati Setianingsih; Ida Hayu Dwimawanti; Asih Widi Lestari; Renata Jati Nirmala (WINDRADI: Jurnal Pengabdian Masyarakat, 2025)
This community service program was conducted as part of the implementation of the Tri Dharma of Higher Education, focusing on strengthening the digital capacity of members of the Family Empowerment and Welfare Movement (Pemberdayaan dan Kesejahteraan Keluarga or PKK) in Turusgede Village, Rembang District, Rembang Regency. The activity stemmed from the existing condition in which PKK data collection was still performed manually, leading to inefficiency, inaccuracies, and difficulties in archiving. To address these challenges, training on the use of Google Forms was introduced as a practical information technology solution to support the digitalization of PKK’s organizational management. The program employed a participatory and hands-on training approach, consisting of several stages: needs assessment, training module development, theoretical and practical sessions, as well as post-training monitoring and evaluation. The evaluation results showed that the training effectively improved participants’ digital literacy and technical skills, as evidenced by their ability to independently create and manage digital forms. Participants responded very positively, showing high enthusiasm and a strong commitment to applying the newly acquired skills in PKK administrative and data collection activities. Despite challenges such as limited access to digital devices and varying levels of digital literacy, the program successfully fostered awareness and confidence among PKK members in utilizing technology. Sustainability efforts include continuous mentoring, the development of practical user guides, and the establishment of local digital cadres within the village. Overall, this program made a tangible contribution to strengthening data-based organizational governance, improving the effectiveness of family empowerment programs, and accelerating digital transformation at the community level.